PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KUALITAS PELAYANAN KOPERASI SIMPAN PINJAM DI KSP HARMONI ARTHA SEJAHTERA ABADI - susilowati, titik (Universitas Sarjanawiyata Tamansiswa, 2025)
This study examines the impact of knowledge management on service quality at KSP Harmoni Artha Sejahtera Abadi, focusing on knowledge transfer and its role in reducing competency gaps. Using a qualitative descriptive method, data were gathered through observation and informal discussions. Findings indicate that knowledge sharing occurs informally and lacks structured training or documentation, resulting in uneven employee competencies. A more systematic knowledge management approach is essential to ensure equitable knowledge distribution and improved service quality.